Play, Algorithmic Thinking and Early Childhood Education: Challenges in the Portuguese Context - Figueiredo, Maria Pacheco (2021)
ALGOLITTLE is an EU-funded project, with partners from Portugal, Italy, Turkey, and Slovenia, supporting the integration of algorithmic thinking skills into preschool education for preparing future code literates from an early age. The paper presents the project and frames it in Portuguese Early Childhood Education. First, in terms of curricular areas and pedagogical approach, through a content analysis of the Portuguese Curricular Guidelines for Preschool Education. Second, by analyzing initiatives and projects that are connected to algorithmic thinking in Early Childhood Education in Portugal. Third, by presenting challenges that emerged from a set of discussions with several participants, highlighting the complexity and timeliness of the project.